Proteasome Inhibition and Combination Therapy for Non-Hodgkin's Lymphoma: From Bench to Bedside - Mato, Anthony R. (AlphaMed Press, 2012)
Although patients with B-cell non-Hodgkin's lymphoma (NHL) usually respond to initial conventional chemotherapy, they often relapse and mortality has continued to increase over the last three decades in spite of salvage therapy or high dose therapy and stem cell transplantation. Outcomes vary by subtype, but there continues to be a need for novel options that can help overcome chemotherapy resistance, offer new options as consolidation or maintenance therapy postinduction, and offer potentially less toxic combinations, especially in the elderly population. The bulk of these emerging novel agents for cancer treatment target important biological cellular processes. Bortezomib is the first in the class of proteasome inhibitors (PIs), which target the critical process of intracellular protein degradation or recycling and editing through the proteasome. Bortezomib is approved for the treatment of relapsed or refractory mantle cell lymphoma. The mechanisms of proteasome inhibition are very complex by nature (because they affect many pathways) and not fully understood. However, mechanisms of action shared by bortezomib and investigational PIs such as carfilzomib, marizomib, ONX-0912, and MLN9708 are distinct from those of other NHL treatments, making them attractive options for combination therapy. Preclinical evidence suggests that the PIs have additive and/or synergistic activity with a large number of agents both in vitro and in vivo, from cytotoxics to new biologicals, supporting a growing number of combination studies currently underway in NHL patients, as reviewed in this article. The results of these studies will help our understanding about how to best integrate proteasome inhibition in the management of NHL and continue to improve patient outcomes.